1988
DOI: 10.1149/1.2095729
|View full text |Cite
|
Sign up to set email alerts
|

Arsine Adsorption on Activated Carbon

Abstract: Activated carbon adsorbs arsine in an inert atmosphere by physical adsorption and chemisorption. The physically adsorbed arsine desorbs readily at room temperature, which must be taken into consideration when activated carbon is used to remove arsine from effluent gas. Chemisorption is facilitated by copper and chromium present on the carbon surface as oxides. During chemisorption the arsine reduces both oxides. Upon exposure to air an exothermal oxidation reaction occurs reverting the copper and arsenic to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 3 publications
0
27
0
Order By: Relevance
“…However, this study was conducted only for removing SiH 4 in the exhaust gas. The optimum composition of metal oxides for treating other toxic hydrides, such as AsH 3 and pH 3 , and SiH 4 in the presence of other hydrides is worth investigating, and the study will be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, this study was conducted only for removing SiH 4 in the exhaust gas. The optimum composition of metal oxides for treating other toxic hydrides, such as AsH 3 and pH 3 , and SiH 4 in the presence of other hydrides is worth investigating, and the study will be conducted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers studied the adsorption of toxic hydride gases, such as AsH 3 and pH 3 . Haacke et al 3 found that activated carbon impregnated with copper and chromium is an effective medium to remove AsH 3 from the effluent gas. They also showed that AsH 3 was oxidized to As 0 , whereas metal Cu 2ϩ , coated on the activated carbon surface, was reduced to Cu 0 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations